THE ANALYSIS OF GREEN BANKING DISCLOSURE: A PERSPECTIVE ON THE BANKING SECTOR IN INDONESIA - Windasari Rachmawati; Abdul Karim; Abdul Manan (Universitas Tidar, 2023)
The aim of this study is to examine the effect of financial performance on green banking disclosure, using control mechanisms as moderating factors. This is a quantitative study with secondary data. The population consists of banking companies listed on the IDX during 2018-2021 with a purposive sampling technique. Financial performance is measured by profitability using two proxies, return on assets (ROA) and return on equity (ROE). GBD is measured using Green Banking Disclosure Index through content analysis. Smart PLS does statistical testing. This study shows that profitability (ROA) affects GBD. Meanwhile, profitability (ROE) does not affect the GBD. Furthermore, the board of commissioners and audit committees moderate the relationship between profitability (ROA and ROE) and GBD. The results provide important insights into the relationship between financial performance, sustainable banking disclosure, and the role of control mechanisms (the board of commissioners and audit committees) in the banking context in Indonesia.